Remotely supervised at-home tDCS for veterans with persistent post-traumatic headache: a double-blind, sham-controlled randomized pilot clinical trial - Charvet, Leigh; Harrison, Adam T.; Mangold, Kiersten; Moore, Robert Davis; Guo, Siyuan; Zhang, Jiajia; Datta, Abhishek; Androulakis, X. Michelle (Frontiers in Neurology, 2023)
Background Currently, there are no FDA approved therapies for persistent post-traumatic headache (PPTH) secondary to traumatic brain injury (TBI). As such neither headache nor TBI specialists have an effective means to manage PPTH. Thus, the objective of the present pilot trial was to evaluate the feasibility and preliminary efficacy of a four-week at-home remotely supervised transcranial direct current stimulation (RS-tDCS) intervention for veterans with PPTH. Methods Twenty-five (m = 46.6 ± 8.7 years) veterans with PPTH were randomized into two groups and received either active (n = 12) or sham (n = 13) RS-tDCS, with anodal stimulation over left dlPFC and cathodal over occipital pole. Following a four-week baseline, participants completed 20–sessions of active or sham RS-tDCS with real-time video monitoring over a period of four-weeks. Participants were assessed again at the end of the intervention and at four-weeks post-intervention. Primary outcomes were overall adherence rate (feasibility) and change in moderate-to-severe headache days per month (efficacy). Secondary outcomes were changes in total number of headache days, and PPTH-related functional outcomes. Results Adherence rate was high with 88% of participants (active = 10/12; sham = 12/13) fully completing tDCS interventions. Importantly, there was no significant difference in adherence between active and sham groups (p = 0.59). Moderate-to-severe headache days were significantly reduced within the active RS-tDCS group (p = 0.004), compared to sham during treatment (−2.5 ± 3.5 vs. 2.3 ± 3.4), and 4-week follow-up (−3.9 ± 6.4 vs. 1.2 ± 6.5). Total number of headache days was significantly reduced within the active RS-tDCS (p = 0.03), compared to sham during-treatment (−4.0 ± 5.2 vs. 1.5 ± 3.8), and 4-week follow-up (−2.1 ± 7.2 vs. −0.2 ± 4.4). Conclusion The current results indicate our RS-tDCS paradigm provides a safe and effective means for reducing the severity and number of headache days in veterans with PPTH. High treatment adherence rate and the remote nature of our paradigm indicate RS-tDCS may be a feasible means to reduce PPTH, especially for veterans with limited access to medical facilities. Clinical Trial Registration: ClinicalTrials.gov, identifier [NCT04012853].